Influence of Parameters on Airside Performance of Wavy Fin-and-tube Heat Exchangers with Hydrophilic Coating under Dehumidifying Conditions - Zhang Yuanming; Ding Guoliang; Ma Xiaokui (Zhileng xuebao, 2007)
The effects of space of fins, number of tube rows and relative humidity of incoming air on airside performance of waw fin with hydrophilic coating under dehumidifying conditions were experimentally explored for seven waw fin - and - tube heat exchangers with hydrophilic coating. The Colburn factor and the Fanning friction were applied to describe airside heat transfer and friction characteristics, respectively. The test results indicate that the Colburn factor and the friction factor increase with the decrease of space of fins. The Colburn factor decreases when number of tube rows increases while the effect of number of tube rows on the friction factor is small. When inlet relative hu- midity increases, the Colbum factor increases and the friction factor almost remains unchanged. Inlet relative humidity has a more significant effect on the Colburn factor when the inlet water temperature is lower.